2021
DOI: 10.3390/ijerph18094811
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Emotional Skills in Adolescence. Influence of Personal and Extracurricular Variables

Abstract: Social-emotional skills have been an important object of study in recent years due to their relationship with academic, personal and professional success. The aim of this study was to analyse the relationship between these skills and different influential variables. The participants had a mean age of 14.18 years. The instruments used were the Social Emotional Competence Questionnaire (SECQ) and the Physical Activity Questionnaire for Adolescents (PACQ-A). Generally, the results indicated gender differences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
(86 reference statements)
1
14
0
9
Order By: Relevance
“…Social and emotional competences positively predicted pupils' academic achievement, including reading, mathematics, and science outcomes in fourth-grade and fifth-grade students (Wang et al, 2019). Amongst other influential variables, decision-making skills appeared to be the most crucial variable in predicting students' academic performance in secondary student populations (Portela-Pino et al, 2021). In addition to that, CASEL found notable benefits of SEL in students' academic outcomes from a meta-analysis of over 200 school-based intervention programmes.…”
Section: Empirical Evidence Supporting Social and Emotional Skillsmentioning
confidence: 92%
“…Social and emotional competences positively predicted pupils' academic achievement, including reading, mathematics, and science outcomes in fourth-grade and fifth-grade students (Wang et al, 2019). Amongst other influential variables, decision-making skills appeared to be the most crucial variable in predicting students' academic performance in secondary student populations (Portela-Pino et al, 2021). In addition to that, CASEL found notable benefits of SEL in students' academic outcomes from a meta-analysis of over 200 school-based intervention programmes.…”
Section: Empirical Evidence Supporting Social and Emotional Skillsmentioning
confidence: 92%
“…However, they reported associations between participation in sport activities and an increase in adaptive behaviour as well as an increase in internalising problems for children whose participation in such activities lasted two or three years. Out-of-home activities differ in their quality and future studies are warranted to consider both quantitative and qualitative aspects of out-of-home activities (see also Durlak et al, 2010 ; Portela-Pino et al, 2021 , for similar recommendations). Furthermore, future studies on relations between HLE, out-of-home activities, and socio-emotional skills might profit from the use of experience sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Molinuevo et al ( 2010 ), sports activities were slightly more relevant for boys, whereas nonsports activities were more related to measures of adjustment in girls. Portela-Pino et al ( 2021 ) found participation in sport activities of adolescents aged between 11 and 18 years to be related to a lower level of socio-emotional skills and suggested the share of negative emotions (e.g., competitiveness, frustrations) which often occur within sport activities as a possible explanation of this result. Thus, overall, participation in out-of-home activities seems to have positive effects for socio-emotional skills in primary school children.…”
Section: Factors Influencing Early Socio-emotional Outcomesmentioning
confidence: 99%
“…Hasil kegiatan ini sesuai dengan uraian bahwa kegiatan luar sekolah berupa pelatihan akan mendukung pengembangan keterampilan sosial emosional bagi siswa. Faktor kesadaran sosial berkembang dengan baik pada dengan adanya pengalaman baru dalam menghasilkan karya yang menarik [7] 4. KESIMPULAN DAN SARAN Dari hasil kegiatan program kemitraan masyarakat dapat disimpulkan bahwa program PKM ini telah meningkatkan pengetahuan siswa tentang pembuatan media interaktif dalam mengembangkan keterampilan bermedia sosial dengan bijak.…”
Section: Pembahasanunclassified